Evidence-Based Strength and Conditioning Plan for Freestyle Snowboarding Athletes. Issue 5 (October 2021) - Dann, Rick A.; Kelly, Vincent
Abstract : ABSTRACT: Competitive snowboarding (SB) has rapidly grown in popularity since its introduction into the Olympics in 1998. This growth has seen a significant increase in trick difficulty and the associated physical demands required for success. Despite the increase in physical requirements, there are currently no evidence-based recommendations that incorporate strength and conditioning or injury prevention programs. This article draws on current research that details the physical demands of SB and integrates relevant strength and conditioning principles to create an evidence-based training plan. This plan highlights the essential physical attributes for snowboard athletes that are important for successful performance and mitigating injury risk.